2008
DOI: 10.1200/jco.2008.17.1157
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Fluorodeoxyglucose Positron Emission Tomography in Nonseminomatous Germ Cell Tumors After Chemotherapy: The German Multicenter Positron Emission Tomography Study Group

Abstract: The presence of vital carcinoma and mature teratoma is common (55%) in residual masses in patients with NSGCT, and CT and STM cannot reliably predict absence of disease. In contrast to prior studies, this prospective trial, which is the only with histologic confirmation in all patients, demonstrated that FDG-PET is unable to give a clear additional clinical benefit to the standard diagnostic procedures, CT and STM, in the prediction of tumor viability in residual masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(64 citation statements)
references
References 32 publications
2
56
0
6
Order By: Relevance
“…However, FDG-PET does not offer any benefit over CT in primary staging performed with the intention of discriminating the nature of the residual masses. Although a positive PET scan is highly suggestive of residual viable cancer, false-negative rates of up to 40% have been reported in a prospective trial by Oechsle et al [12] In contrary, PET scan has more utility in patients with disseminated seminoma treated with chemotherapy where it has a higher sensitivity and specificity for the determination of residual viable disease. [13] Although the germ cell tumor is highly responsive to chemotherapy, the success rate of chemotherapy is lower after failure of the first-line chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…However, FDG-PET does not offer any benefit over CT in primary staging performed with the intention of discriminating the nature of the residual masses. Although a positive PET scan is highly suggestive of residual viable cancer, false-negative rates of up to 40% have been reported in a prospective trial by Oechsle et al [12] In contrary, PET scan has more utility in patients with disseminated seminoma treated with chemotherapy where it has a higher sensitivity and specificity for the determination of residual viable disease. [13] Although the germ cell tumor is highly responsive to chemotherapy, the success rate of chemotherapy is lower after failure of the first-line chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…In studies investigating the live tumor presence by PET-CT 70% sensitivity, 48% specificity, 59% positive predictive value and 51% negative predictive value was obtained. PET-CT revealed no uptake in patients with teratoma (18). While there are studies arguing that low attenuation levels in CT predict necrosis, but there are also other studies that don't support this idea (10,19,20).…”
Section: Discussionmentioning
confidence: 98%
“…The authors of several investigations agree that 18 F-FDG PET predicts viable residual tumor with high diagnostic accuracy, except in small residuals. However, 18 F-FDG PET failed to differentiate mature teratoma from necrosis or fibrosis because both accumulate little or no 18 F-FDG (7,9,11,33). Therefore 18 F-FDG PETnegative residual tumors still require surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies assessing the role of 18 F-FDG PET in seminomas found a significant advantage of this modality over CT in evaluating postchemotherapy residues. However, the role of 18 F-FDG PET in staging nonseminomatous residues is limited because 18 F-FDG PET cannot differentiate mature teratoma from necrosis and fibrosis (6,7,(9)(10)(11)(12). In predicting early therapy response, 18 F-FDG PET may have a role in poorprognosis GCT patients, as has been addressed in a pilot study with 19 patients (13,14).…”
mentioning
confidence: 99%